THE UTILIZATION OF CANVA DIGITAL MEDIA IN INTEGRATING GRADUATE PROFILE DIMENSIONS AT SMAN 1 LAWANG KIDUL - Laysa Zahran; Siska Wulandari; Anna Damayanti; Jossiselfiah; Zuhdiyah; Asri Karolina (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to describe the use of the digital media Canva in integrating the dimensions of the graduate profile in learning activities at SMAN 1 Lawang Kidul. The research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the use of Canva in learning effectively integrates the dimensions of the graduate profile in a systematic and contextual manner through project-based digital learning. Canva encourages active student engagement in understanding learning materials, expressing ideas creatively, developing critical thinking skills, collaborating, and enhancing independence and communication skills. In addition, digital mediabased learning supports the strengthening of faith based values, citizenship awareness, and digital ethics. Despite several technical constraints, such as limited devices and varying levels of students’ digital skills, overall the use of Canva contributes positively to the development of students’ character and competencies in accordance with the graduate profile dimensions. Therefore, Canva can be considered an innovative learning medium that is relevant to the demands of education in the era society 5.0.